HALAL STANDARD - AN OPPORTUNITY FOR FOOD PRODUCERS IN SERBIA IN THE CURRENT GLOBAL FOOD CRISIS : DOI: 10.5937/etp2402098K - Kalač, Edin; Samardžić, Veljko (Ekonomija - teorija i praksa, 2024)
n the context of the current global food crisis, which is caused by a combination of climate change, geopolitical tensions and economic disruptions, the need for market diversification and adaptation of production standards becomes imperative for food producers The paper analyses the Halal market, which is considered to be one of the fast-growing markets with a large consumer base and the requirements that interested food producers must meet in order to adapt their production to this standard. The aim of the paper is to explore the potential of the Halal standard as a strategy for expanding the market and increasing the competitiveness of food producers in Serbia. Using descriptive analysis, the importance of this standard in the context of the global crisis caused by current conflicts is highlighted, affecting most Muslim countries that import food from abroad. It is concluded that Halal certification can be a sustainable strategy for overcoming current challenges in food production and trade, emphasizing its relevance not only for Muslim consumers but also for the global market, which increasingly values transparency, quality, and ethical production.